Two new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China and Vietnam - Gyulai, Peter; Ronkay, László; Ronkay, Gábor; Saldaitis, Aidas (Zootaxa, 2015)
The genus Phlogophora Treitschke (type species Phlogophora meticulosa (Linnaeus)) comprises some 60 known species. Phlogophora is a widely distributed genus, mostly with Trans-Palaearctic and Oriental distribution, however species of the genus are known from the Ethiopian Region, and some from the Nearctic, as well. Phlogophora displays the highest diversity from the monsoon influenced regions of the Central and Southern Himalaya (Nepal, India, Myanmar and Vietnam) to the Indonesian islands in the South. A number of the species are endemic in islands from the Azores throughout Madagascar, Taiwan and, particularly, in the Sundaland (The Philippines and the Sunda Islands, towards to the east to New Guinea).